1999
DOI: 10.1007/s001050050901
|View full text |Cite
|
Sign up to set email alerts
|

Bade-PUVA-Therapie bei Granuloma anulare

Abstract: Sixteen patients with generalized granuloma anulare and two patients with localized granuloma anulare received bath-PUVA therapy. Their lesions previously had not responded to conventional therapy. After an average of 55 (11 to 61) treatments and a mean cumulative dose of 69.5 (7.1 to 261.5) J/cm2, complete remission was observed in 5 patients and a clear improvement in 10 patients. Three patients stopped therapy after few treatments. Recurrent lesions appeared in 4 patients; in three of them reinitiation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 13 publications
(15 reference statements)
0
15
0
3
Order By: Relevance
“…Nach durch schnitt lich 55 Be hand lun gen (durch schnitt li che ku mu la ti ve UVA-Do sis: 69,5 J/cm 2 ) wa ren die Lä sio nen bei 5 Pa ti enten voll stän dig und bei 10 wei te ren weit ge hend ab ge heilt; 3 Pa ti en ten, da run ter ei ner mit lo ka li sier ter Form der Er kran kung, bra chen die The ra pie früh zei tig ab. Bei 4 der Re sponder kam es nach The ra pie en de zu ei nem Re zi div, nach er neu ter The ra pie wie der zu einer kli ni schen Ab hei lung [23].…”
Section: Pho To Che Mo the Ra Pieunclassified
“…Nach durch schnitt lich 55 Be hand lun gen (durch schnitt li che ku mu la ti ve UVA-Do sis: 69,5 J/cm 2 ) wa ren die Lä sio nen bei 5 Pa ti enten voll stän dig und bei 10 wei te ren weit ge hend ab ge heilt; 3 Pa ti en ten, da run ter ei ner mit lo ka li sier ter Form der Er kran kung, bra chen die The ra pie früh zei tig ab. Bei 4 der Re sponder kam es nach The ra pie en de zu ei nem Re zi div, nach er neu ter The ra pie wie der zu einer kli ni schen Ab hei lung [23].…”
Section: Pho To Che Mo the Ra Pieunclassified
“…Bath-water PUVA with 8-MOP has been shown to be beneficial for many skin disorders: psoriasis (12), granuloma anulare (13), atopic dermatitis (14), lichen planus (15), lichen sclerosus et atrophicans (16), localized scleroderma (17), chronic palmoplantar eczema (18,19) and lymphomatoid papulosis (20). Comparative studies in psoriasis showed that bath-water PUVA is as effective as oral PUVA but requires less cumulative UVA (12,21,22).…”
mentioning
confidence: 97%
“…Similar risks are faced with bath PUVA therapy or phototherapy with UVA1, the two methods used successfully to combat this disorder. 2–3 …”
mentioning
confidence: 99%